STUDIES ON INTESTINAL HELMINTHIASIS IN, NORTH-EAST OF IRAN - F. Arfaa; E. Kayvan; E. Ghadirian; G.H. Missaghian (Tehran University of Medical Sciences, 1977)
Prevalence of various intestinal helminthiasis has been established among the population of 42 villages in Gonbad Kavus in the north-east of the Caspian Littoral during a longitudinal health survey undertaken in this area. Stool examination by formaline ether technique been performed among 1240 randomly selected population. Surprisingly and contrary to most other areas in Iran; very low infection rate With Ascaris (0.2%), Trichostrongylus (1.2%), hookworm (2.4%) and Trichuris (0.2%) were foundt among the population. Prevalence of infection with Hymenolepis nana was rather high (overall prevalence. of 12.5%). Significant variation has only been observed in the prevalence of Hymenolepis nana in various age groups. Simultaneous infection with two or more helminths has been found in 16.5% of people and 9.6% were infected with one, worm. Infection with all helminths except Hymenolepis was very low in 20 villages where 20 or more people were examined. Strongyloides stercoralis with a maximum rate of infection of 4% was found among the population of 5 out of 20 villages. Dicrocoelium dendriticum was also found in 7 persons. Reasons for low prevalence of helminthiasis and its reverse correlation with the high incidence of 4 esophageal cancers in that area are discussed.